Frequency of in Stent Restenosis in Diabetic and Patients Undergoing PCI at Tertiary Care Cardiac Center - Seema Nazir Khattak, Syed Waqas Aslam Naqvi, Shafi Ullah, Muhammad Shahid, Muhammad Mohsin Ayaz, Eshakhan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of in-stent restenosis in diabetic patients undergoing primary percutaneous coronary intervention (PCI). Study Design: Retrospective/Observational study Place and Duration: Department of Adult Cardiology, Peshawar Institute of Cardiology, Peshawar KPK During the Period from January, 2022 to June, 2022. Methodology: Total 380 patients of either gender with ages 25-70 years underwent primary percutaneous coronary intervention were enrolled. Patients were divided into two groups, diabetic (n=180) and non-diabetic (n=200). Detailed demographics including age, sex, BMI, hypertension, family history of ischemic heart disease and smoking status were recorded after taking informed written consent. Patients were followed to examine the incidence of restenosis. Data was analyzed by SPSS 24.0. Results: There were 140 (77.78%) males and 40 (22.22%) females with mean age 48.26±9.55 years in diabetic group and in non-diabetic group 148 (74%) patients were males and 52 (26%) were females with mean age 47.85±10.66 years. Overall frequency of in-stent restenosis was 28 (7.37%), among them 25 (89.29%) were diabetic and 3 (10.71%) were non-diabetic. There was a significant association between diabetes and in-stent restenosis with p-value <0.05. Conclusion: It is concluded that frequency of in-stent restenosis was high and significantly associated with diabetes in patients undergoing primary PCI. Keywords: Percutaneous Coronary Intervention (PCI), Diabetes, In-stent Restenosis